A nanosheet sulfur-doped molybdenum-based catalyst and its preparation method and application
By preparing nanosheet-shaped sulfur-doped molybdenum-based catalysts, using foam nickel as a support and hydrothermal reaction to form a uniform nanosheet-like structure, the problem of poor catalytic performance of existing non-precious metal-based catalysts is solved, and catalytic hydrogenation activity is significantly improved. Element utilization.
Patent Information
- Application Number
- CN202211477605.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-23
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-11-23
AI Technical Summary
Existing non-precious metal-based catalysts have poor catalytic performance in catalytic hydrogenation saturation reactions, especially when treating densely ring aromatic hydrocarbons.
Using a nanosheet-shaped sulfur-molybdenum-based catalyst, hydrothermal reaction is carried out by hydrothermal reaction with ammonium molybdate tetrahydrate, thiourea, urea, ammonium fluoride and non-precious metal nitrates with nickel foam as support to form a catalyst with a uniform nanosheet-like structure. .
The catalytic hydrogenation activity of the catalyst was significantly improved, and the conversion rate of pyrene increased from the original 13.02% to 70.18%. Due to the three-dimensional structure of the support, the dispersion of the active species was uniform, which improved the element utilization rate and catalytic effect.
Smart Images

Figure CN116273069B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coal tar high-temperature fraction catalysis, and specifically relates to a nano-sheet sulfur-doped molybdenum-based catalyst and a preparation method and application thereof. Background Art
[0002] Coal tar, as the main product of coal pyrolysis, is a dark brown mixture with extremely complex composition. It contains a large amount of aromatic hydrocarbons, phenols, aliphatic hydrocarbons, etc., and can be used to process and prepare a variety of chemical products. In addition, coal tar can be hydrogenated to prepare fuels such as gasoline and diesel. Therefore, catalytic hydrogenation technology can effectively improve the use value of coal tar, make up for the shortage of petroleum resources, solve the problem of clean utilization of coal tar, and has certain economic benefits.
[0003] High-temperature coal tar is distilled and cut according to the distillation temperature to obtain fractions in different temperature ranges. Studies have found that gasoline and other fuel oils can be prepared by catalytic hydrogenation of polycyclic aromatic hydrocarbons in the high-temperature fraction of coal tar. However, in the absence of a catalyst, the hydrogenation reaction of polycyclic aromatic hydrocarbons is difficult to carry out, so the study of catalysts for hydrogenation saturation of polycyclic aromatic hydrocarbons is crucial.
[0004] At present, the catalyst used for catalytic hydrogenation saturation is mainly divided into two categories: noble metal-based catalysts (Pd, Pt, etc.) and non-noble metal-based catalysts (Ni, Mo, Co, etc.). Although noble metal-based catalysts have excellent catalytic activity, they are easily poisoned, have poor stability, are easily poisoned by sulfur in coal tar, and are expensive and costly. However, non-noble metal-based catalysts not only have good hydrogenation activity, are widely available, are cheap, and can be prepared and applied in large quantities. Therefore, the excellent catalytic performance of non-noble metal-based catalysts relative to noble metal-based catalysts still needs to be further improved. Summary of the invention
[0005] In order to overcome the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a nano-sheet sulfur-doped molybdenum-based catalyst and a preparation method and application thereof, so as to solve the technical problem of poor catalytic performance of non-precious metal-based catalysts.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The invention discloses a method for preparing a nano-sheet sulfur-doped molybdenum-based catalyst, comprising the following steps:
[0008] S1: mixing and stirring ammonium molybdate tetrahydrate, thiourea, urea, ammonium fluoride, non-precious metal nitrate and deionized water to obtain a mixed solution; placing nickel foam in the mixed solution to perform a hydrothermal reaction to obtain a catalyst precursor;
[0009] Alternatively, ammonium molybdate tetrahydrate, urea, ammonium fluoride, non-precious metal nitrate and deionized water are mixed and stirred to obtain a mixed solution; the nickel foam is placed in the mixed solution, and a hydrothermal reaction is performed to obtain a reaction product; the reaction product is placed in an aqueous solution containing thiourea, and a hydrothermal reaction is performed again to obtain a catalyst precursor;
[0010] S2: The catalyst precursor is calcined to obtain a nanosheet-shaped sulfur-doped molybdenum-based catalyst.
[0011] Furthermore, in S1, the usage ratio of the ammonium molybdate tetrahydrate, thiourea, urea, ammonium fluoride, non-precious metal nitrate and deionized water is (1-4) mmol: (10-10) mmol: (0.5-5) mmol: (0.5-5) mmol: (0-2) mmol: 20 mL.
[0012] Furthermore, in S1, the nickel foam is cut into (2*2~4*4) cm before use. 2 The size of the sample was then ultrasonically treated with a hydrochloric acid solution with a concentration of (3-5) mol / L for 15-20 min, and finally rinsed and dried with anhydrous ethanol and distilled water in turn.
[0013] Furthermore, the nickel foam is placed vertically in the mixed solution to perform a hydrothermal reaction.
[0014] Furthermore, in S1, the stirring time is 10 to 20 minutes.
[0015] Furthermore, in S1, the temperature of the hydrothermal reaction is 120-180° C., and the time is 4-12 hours.
[0016] Furthermore, in S2, the calcination temperature is 300-400°C and the time is 2-3h; the non-precious metal nitrate is a nitrate containing nickel, cobalt, copper or iron.
[0017] Furthermore, the non-precious metal nitrate is cobalt nitrate hexahydrate.
[0018] The invention also discloses a nano-sheet-shaped sulfur-doped molybdenum-based catalyst prepared by the preparation method.
[0019] The invention also discloses the application of the nano-sheet-shaped sulfur-doped molybdenum-based catalyst. The nano-sheet-shaped sulfur-doped molybdenum-based catalyst is used in catalytic hydrogenation saturation reaction.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The invention discloses a method for preparing a nano-sheet sulfur-doped molybdenum-based catalyst. The method adopts ammonium molybdate tetrahydrate, thiourea, urea, ammonium fluoride and non-precious metal nitrate as raw materials, uses nickel foam as a carrier, and uses Mo as an active substance. A three-dimensional structure is provided at a site where active species can grow, and finally a uniform nano-sheet structure is formed, so that the active species are evenly dispersed. At the same time, the nano-sheet molybdenum species has a specific crystal form, which can provide specific reaction active sites required for the reaction, thereby improving the catalytic hydrogenation activity of the catalyst.
[0022] The present invention also discloses a nano-sheet-shaped sulfur-doped molybdenum-based catalyst prepared by the above-mentioned preparation method. Since the three-dimensional macroporous skeleton of the carrier nickel foam provides the growth and dispersion of the nano-sheet-shaped molybdenum-based active species, compared with conventional supported catalysts, the loading amount of the active species loaded on the nickel foam is reduced and the distribution is uniform, which not only improves the element utilization rate, but also makes the catalytic effect of this type of catalyst significant.
[0023] The present invention also discloses the application of the above-mentioned nanosheet sulfur-doped molybdenum-based catalyst in catalytic hydrogenation saturation reaction. According to relevant experimental results, the catalytic activity of the molybdenum-based catalyst is significantly improved after sulfur doping, that is, the conversion rate of the polycyclic aromatic hydrocarbon compound pyrene is increased from the original 13.02% (MoO2 / NF) to 70.18% (CoMoS / NF), and it has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a SEM image of the nanosheet-shaped sulfur-doped molybdenum-based catalyst prepared by the present invention;
[0025] Figure 2 This is the SEM image of the molybdenum-based catalyst prepared in Comparative Example 1. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0027] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0028] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0029] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0030] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0031] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0032] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0033] Example 1
[0034] A method for preparing a nano-sheet sulfur-doped molybdenum-based catalyst comprises the following steps:
[0035] S1: First, the nickel foam is cut into a size of 2cm*2cm, and subjected to ultrasonic treatment in a hydrochloric acid solution with a concentration of 3moL / L for 15min. After the ultrasonic treatment, it is rinsed with anhydrous ethanol and distilled water in turn, and dried for later use;
[0036] 2mmol of ammonium molybdate tetrahydrate, 2mmol of thiourea, 5mmol of urea, 4mmol of ammonium fluoride and 20mL of deionized water were mixed and stirred for 20min to obtain a mixed solution, and the mixed solution was placed in a reactor; the treated nickel foam was fixed in the lining of the reactor so that it was vertically immersed in the mixed solution, and then placed in an oven at a constant temperature of 120°C for 12h for hydrothermal reaction, and a catalyst precursor was obtained after the reaction was completed;
[0037] The catalyst precursor was placed in a muffle furnace and calcined at 350°C for 2 hours to obtain a nanosheet-shaped sulfur-doped molybdenum-based catalyst (MoS / NF).
[0038] Example 2
[0039] A method for preparing a nano-sheet sulfur-doped molybdenum-based catalyst comprises the following steps:
[0040] S2: First, the nickel foam is cut into a size of 2cm*2cm, and subjected to ultrasonic treatment in a hydrochloric acid solution with a concentration of 3 mol / L for 15 min. After the ultrasonic treatment, it is rinsed with anhydrous ethanol and distilled water in turn, and dried for later use;
[0041] 2mmol of ammonium molybdate tetrahydrate, 5mmol of urea, 4mmol of ammonium fluoride and 20mL of deionized water were mixed and stirred for 20min to obtain a mixed solution, which was placed in a reactor; the treated nickel foam was fixed in the lining of the reactor so that it was vertically immersed in the mixed solution, and then placed in an oven at a constant temperature of 120°C for 12h for hydrothermal reaction, and a catalyst precursor was obtained after the reaction; the obtained catalyst precursor was placed in 20mL of thiourea solution (0.1mol / L) for hydrothermal reaction again at a constant temperature of 120°C for 12h.
[0042] Finally, the catalyst precursor was placed in a muffle furnace and calcined at 350°C for 2 hours to obtain a nanosheet-shaped sulfur-doped molybdenum-based catalyst (Mo-S / NF).
[0043] Example 3
[0044] A method for preparing a nano-sheet sulfur-doped molybdenum-based catalyst comprises the following steps:
[0045] S3: First, the nickel foam is cut into a size of 2 cm*2 cm, and subjected to ultrasonic treatment in a hydrochloric acid solution with a concentration of 3 mol / L for 15 min. After the ultrasonic treatment, it is rinsed with anhydrous ethanol and distilled water in turn, and dried for later use;
[0046] 2mmol of ammonium molybdate tetrahydrate, 2mmol of thiourea, 5mmol of urea, 4mmol of ammonium fluoride, 2mmol of cobalt nitrate hexahydrate and 20mL were mixed and stirred for 20min to obtain a mixed solution, and the mixed solution was placed in a reactor; the treated nickel foam was fixed in the lining of the reactor so that it was vertically immersed in the mixed solution, and then placed in an oven at 120°C for 12h for hydrothermal reaction, and a catalyst precursor was obtained after the reaction was completed;
[0047] The catalyst precursor was placed in a muffle furnace and calcined at 350°C for 2 hours to obtain a nanosheet-shaped sulfur-doped molybdenum-based catalyst (MoCoS / NF).
[0048] Example 4
[0049] A method for preparing a nano-sheet sulfur-doped molybdenum-based catalyst comprises the following steps:
[0050] S4: First, the nickel foam is cut into a size of 2 cm*2 cm, and subjected to ultrasonic treatment in a hydrochloric acid solution with a concentration of 3 mol / L for 20 min. After the ultrasonic treatment, it is rinsed with anhydrous ethanol and distilled water in turn, and dried for later use;
[0051] 2mmol of ammonium molybdate tetrahydrate, 5mmol of urea, 4mmol of ammonium fluoride, 2mmol of cobalt nitrate hexahydrate and 20mL were mixed and stirred for 20min to obtain a mixed solution, which was placed in a reactor; the treated nickel foam was fixed in the lining of the reactor so that it was vertically immersed in the mixed solution, and then placed in an oven at a constant temperature of 120°C for 12h for hydrothermal reaction, and a catalyst precursor was obtained after the reaction; the obtained catalyst precursor was placed in 20mL of thiourea solution (0.1mol / L) for hydrothermal reaction again, and the mixture was heated at 120°C for 12h.
[0052] The catalyst precursor was placed in a muffle furnace and calcined at 350°C for 2 hours to obtain a nanosheet-shaped sulfur-doped molybdenum-based catalyst (MoCo-S / NF).
[0053] Comparative Example 1
[0054] A method for preparing a molybdenum-based catalyst comprises the following steps:
[0055] S1: First, the nickel foam is cut into a size of 2cm*2cm, and subjected to ultrasonic treatment in a hydrochloric acid solution with a concentration of 3moL / L for 15min. After the ultrasonic treatment, it is rinsed with anhydrous ethanol and distilled water in turn, and dried for later use;
[0056] 2mmol of ammonium molybdate tetrahydrate, 5mmol of urea, 4mmol of ammonium fluoride and 20mL were mixed and stirred for 20min to obtain a mixed solution, and the mixed solution was placed in a reactor; the treated nickel foam was fixed in the lining of the reactor so that it was vertically immersed in the mixed solution, and then placed in an oven at a constant temperature of 120°C for 12h for hydrothermal reaction, and a catalyst precursor was obtained after the reaction was completed;
[0057] The catalyst precursor was placed in a muffle furnace and calcined at 350°C for 2 hours to obtain a molybdenum-based catalyst (MoO2 / NF).
[0058] Figure 1 and Figure 2 The SEM morphologies of MoS / NF, Mo-S / NF, MoCoS / NF, MoCo-S / NF prepared in Examples 1, 2, 3, 4 and MoO2 / NF prepared in Comparative Example 1 respectively show that the molybdenum-based catalyst with nickel foam as the carrier has a uniform nanosheet structure, and the sulfur-doped bimetallic MoCoS / NF catalyst has a more uniform petal-like nanosheet structure.
[0059] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a nano-sheet sulfur-doped molybdenum-based catalyst, characterized in that: The following steps are involved: S1: mixing and stirring ammonium molybdate tetrahydrate, thiourea, urea, ammonium fluoride, non-precious metal nitrate and deionized water to obtain a mixed solution; placing nickel foam in the mixed solution to perform a hydrothermal reaction to obtain a catalyst precursor; Alternatively, ammonium molybdate tetrahydrate, urea, ammonium fluoride, non-precious metal nitrate and deionized water are mixed and stirred to obtain a mixed solution; the nickel foam is placed in the mixed solution, and a hydrothermal reaction is performed to obtain a reaction product; the reaction product is placed in an aqueous solution containing thiourea, and a hydrothermal reaction is performed again to obtain a catalyst precursor; S2: calcining the catalyst precursor to obtain a nanosheet-shaped sulfur-doped molybdenum-based catalyst; In S1, the usage ratio of the ammonium molybdate tetrahydrate, thiourea, urea, ammonium fluoride, non-precious metal nitrate and deionized water is (1-4) mmol: 2 mmol: (0.5-5) mmol: (0.5-5) mmol: 2 mmol: 20 mL; In S1, the temperature of the hydrothermal reaction is 120-180° C., and the time is 4-12 hours.
2. The method for preparing a nano-sheet sulfur-doped molybdenum-based catalyst according to claim 1, characterized in that: In S1, the nickel foam is cut into (2*2~4*4) cm before use. 2 The size of the sample was then ultrasonically treated with a hydrochloric acid solution with a concentration of (3~5) mol / L for 15~20 minutes, and finally rinsed and dried with anhydrous ethanol and distilled water in turn.
3. The method for preparing a nano-sheet sulfur-doped molybdenum-based catalyst according to claim 2, characterized in that: The nickel foam is vertically placed in the mixed solution to perform a hydrothermal reaction.
4. The method for preparing a nano-sheet sulfur-doped molybdenum-based catalyst according to claim 1, characterized in that: In S1, the stirring time is 10 to 20 minutes.
5. The method for preparing a nano-sheet sulfur-doped molybdenum-based catalyst according to claim 1, characterized in that: In S2, the calcination treatment is carried out at a temperature of 300-400°C for 2-3 hours; and the non-precious metal nitrate is a nitrate containing nickel, cobalt, copper or iron.
6. The method for preparing a nano-sheet sulfur-doped molybdenum-based catalyst according to claim 5, characterized in that: The non-noble metal nitrate is cobalt nitrate hexahydrate.
7. A nanosheet-shaped sulfur-doped molybdenum-based catalyst, characterized in that: The catalyst is prepared by the method for preparing a nano-sheet-shaped sulfur-doped molybdenum-based catalyst as described in any one of claims 1 to 6.
8. The use of a nano-sheet sulfur-doped molybdenum-based catalyst according to claim 7, characterized in that: The nanosheet-shaped sulfur-doped molybdenum-based catalyst is used in catalytic hydrogenation saturation reaction.